2009
DOI: 10.1176/appi.ap.33.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Preventive, Lifestyle, and Personal Health Behaviors Among Physicians

Abstract: Additional interventions designed to improve physicians' lifestyles and personal health behaviors should be encouraged. A focus on creating healthy lifestyles will benefit physicians as much as the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 34 publications
3
78
1
6
Order By: Relevance
“…In addition, 34% reported 6 or fewer hours of sleep daily, while 21% self-reported working more than 60 hours per week. Physicians' excessive number of work hours(more than 65 hours per week) was associated with lack of exercise, not eating breakfast, and sleeping fewer than 6 hours per night (7).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, 34% reported 6 or fewer hours of sleep daily, while 21% self-reported working more than 60 hours per week. Physicians' excessive number of work hours(more than 65 hours per week) was associated with lack of exercise, not eating breakfast, and sleeping fewer than 6 hours per night (7).…”
Section: Discussionmentioning
confidence: 98%
“…Also, physicians disregard keeping a healthy diet and exercise habits for themselves, perhaps due to feeling protected by their own knowledge and sometimes under-diagnose their own overweight status and even display lower rates of healthy behaviours compared with the general population (6). Furthermore, physicians' excessive number of work hours(mo re than 65 hours per week) was associated with lack of exercise, not eating breakfast, and sleeping fewer than 6 hours per night (7).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that issues such as work-life balance, social and family support, adequate rest, and regular physical activity correlate with career satisfaction, improved sense of well-being, increased empathy, and decreased burnout. 37,38 As opposed to physicians who neglect their health, 39 physicians with healthy lifestyle habits have been perceived as more credible and motivating to their patients and the residents under their supervision. [40][41][42] It has been shown that wellness behaviors in physicians are additive; therefore, individuals should be encouraged to adopt a variety of approaches to best suit their individual needs.…”
Section: The Components Of Wellnessmentioning
confidence: 99%
“…13 Bazargan M et al reported that 35% of participants reported "no" or "occasional" exercise. 14 In present study, out of 100 male doctors, 20 (20%) were physician, 18 (18%) were surgeons, 11 (11%) were anesthetists, 8 (8%) were pediatricians, 7 (7%) were Orthopedicians, 6 (6%) were gynecologists, , 6 (6%) were pathologists, 6 (6%) were radiologists, 6 (6%) were ophthalmologists, 6 (6%) were ENT Surgeons, 2 (2%) were general practitioners while 1(1%) each were pulmonologist, Neurosurgeon, Gastroenterologist and Pediatric Surgeon (Table 5). …”
mentioning
confidence: 99%